Performance of anaerobic baffled reactor (ABR) in treating domestic wastewater - Adnan, Nur Hidayah (2003)
Performance of a laboratory-scale Anaerobic Baffled Reactor (ABR) system treating chemically adjusted domestic (sewage) wastewater with variable strength of 100-500 mg/L was investigated at anaerobic condition (25-30 °C) for 81 days after reaching steady-state at different retention time of 1 d, 2 d and 3 d. The evaluation was made by assuming a series of plug flow growth reactor, so that the results did not give a realistic interpretation of the data since diffusional limitations were not considered. The experimental section shows that for all wastewater strength, maximum COD removal of 69% were obtained at loading rates of 0.102-0.306 kg. COD/m3.day have been reported in the literature review. Removal efficiencies showed very little sensitivity to daily fluctuations in influent wastewater quality. HRT, pH and wastewater strength have a significant impact on sulfate removal, and longer retention time, lower pH and wastewater strength resulted in higher sulfate removal, contrary with nitrite where at longer retention time and lower pH and wastewater strength there would be an addition in nitrite. Overall, the ABR like other anaerobic reactors was not an efficient reactor for anions removal. The main objectives of this study was to study the ability of Anaerobic Baffled Reactor (ABR) to remove organics from domestic wastewater, as well as to investigate the possibility of ABR as an efficient, economic and lowly operation and maintenance, which do not need expertise to handle, compared to other systems. In order to enhance the commercial potential of ABR, more work still remains to be done in the following area: COD removal, solids, treatment of toxic wastewater and an improved understanding of the factors controlling bacterial ecology.